Polystyrene blends: a rheological and solid-state study of the role of molecular weight distribution - Sánchez Valencia, Andrea (2018)
Commercial polymers are typically classified according to their melt flow indices, measures of their viscosities. These properties are known to depend on a material’s molar mass distribution, on its averages and its degree of polydispersity. In determining a polymer’s performance, both the molar mass distribution and the process employed to produce the part are highly relevant, since the balance in the mass fractions from its distribution will determine the flow characteristics in the mould, and influence the material’s performance. The compromise polymer manufacturers have to make is to maintain the mechanical properties known to improve with increased molar mass at the same time as a sufficiently low viscosity, known to reduce with decreasing molar mass, to enable part production. This is often achieved by judicious blending of homopolymers. This thesis examines how varying molar mass and distribution in blends leads to changes in the thermal, rheological, and mechanical properties in polystyrene, and discusses and develops physical models to capturing the observed experimental responses.